Information resources on comics. State of the question - Castillo-Vidal, Jesús (Anuario ThinkEPI, 2010)
Although the comic has been with us much longer than other arts considered as such without prejudice, there are currently no appropriate search tools that allow us to study this publication genre, so there is a considerable information vacuum in this respect. We briefly discuss the reasons that led to this neglect, and how to end this vicious circle that increasingly isolates the comic from the other arts.
Keywords: Comics; Arts; Literature; Literary genres; Information sources; Prejudice; Acceptance; Society; Weblogs; Journals; Libraries; Databases.